El mito en Génesis VI: 1-4 (Argos, 2025)
This article aims to show the complexity of Genesis VI: 1-4. The Yahwist, author of the oldest stratum of biblical narrative, makes use of a mythological fragment, displaced from its traditional context and integrated into the structural and thematic framework of Genesis l-Xl. The essential features of this myth (the flood, separation of God from mortal men) can be traced in an unbroken continuum on near eastern soil from the midsecond millenium. Hesiod and the Homeric epic pursue similar temes in the description of the separation of the heroic demigods from the mortal men.
Keywords: Yahweh; myth; mortals; gods; heroes